FILSAFAT ILMU DALAM PERKEMBANGAN BASIS STANDAR AKUNTANSI: RULES BASED MENJADI PRINCIPLE BASED - Nurlaila Maysaroh Chairunnisa; Khomsiyah Khomsiyah (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Islam 45, 2022)
Accounting science is part of the philosophy of science, which according to Thomas Khun a science can not be separated from the paradigm revolution. This article aims to explain the development of the basis of accounting standards in Indonesia, which was originally rules based and shifted to principle based. The method used in this article is a literature study. An analytical tool for Khun's paradigm revolution in science that occurred in the development of the basis of accounting standards. The results of this article explain that rules based is a paradigm and prior knowledge. Then the emergence of anomalies in the form of fraudulent financial statement presentations and the existence of globalization created a crisis. The crisis will be the basis of the accounting standards used. IFRS with principles based is a new paradigm and a solution to the crisis. Until now, principle based has become a new knowledge in accounting science.